2016
DOI: 10.3390/e18050177
|View full text |Cite
|
Sign up to set email alerts
|

Fatiguing Effects on the Multi-Scale Entropy of Surface Electromyography in Children with Cerebral Palsy

Abstract: Abstract:The objective of this study was to investigate the effects of muscle fatigue on the multi-scale entropy of surface electromyography (EMG) in children with cerebral palsy (CP) and typical development (TD). Sixteen CP children and eighteen TD children participated in experiments where they performed upper limb cyclic lifting tasks following a muscle fatiguing process, while the surface EMG signals were recorded from their upper trapezius muscles. Multi-scale entropy (MSE) analyses of the surface EMG wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 51 publications
1
27
1
Order By: Relevance
“…The coefficient curves can further reveal the abnormal MU activation patterns during crawling in CP. Some researchers have found that motor dysfunction of CP manifested as abnormal entropy of multi-scale oscillations of sEMG activities in CP, and a major peripheral cause of these abnormalities is abnormal MU recruitment ( 10 , 16 ). This study revealed that motor dysfunction of CP also manifested as abnormal recruitment of oscillation synergies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coefficient curves can further reveal the abnormal MU activation patterns during crawling in CP. Some researchers have found that motor dysfunction of CP manifested as abnormal entropy of multi-scale oscillations of sEMG activities in CP, and a major peripheral cause of these abnormalities is abnormal MU recruitment ( 10 , 16 ). This study revealed that motor dysfunction of CP also manifested as abnormal recruitment of oscillation synergies.…”
Section: Discussionmentioning
confidence: 99%
“…Gross et al ( 8 ) found that co-activation index of the rectus femoris/semitendinosus couple was more sensitive to speed, which could be explained by altered motor control. Furthermore, increasing studies suggested that the motor dysfunction caused by CP affected not only the overall sEMG activity but also the sEMG frequency components or oscillations ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSE is used to calculate the sample entropy on multiple scales of the original signal and it is obtained by using a coarse granulation process at different scales [ 44 , 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The empirical mode decomposition (EMD) (Shang et al, 2011 ; Hong et al, 2016 ) was employed to extract multichannel-recorded sEMG features for pattern recognition. In each trial, a 4-second-recorded sEMG was extracted per channel, and the EMD was used to decompose the sEMG into eight intrinsic mode functions (IMFs) as where r is the residual component, means the central tendency of sEMG signal.…”
Section: Methodsmentioning
confidence: 99%